ANALISIS PENGARUH KOMBINASI RELAKSASI BENSON DAN AROMATERAPI TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MAGELANG TENGAH - Rachmawati, Asa Diah; Ari Murti Widigdo, Dwi; Yulistanti, Yeni; Sarwono, Bambang (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
Hypertension is a condition characterized by elevated blood pressure, which can occur at any time and affect anyone. If left untreated, hypertension can lead to complications such as heart disease, kidney failure, and stroke. Prevention efforts can be undertaken through pharmacological and non-pharmacological approaches. One non-pharmacological management technique is the combination of Benson relaxation and aromatherapy. The aim of this study is to determine the effect of the combination of Benson relaxation and aromatherapy on blood pressure in hypertensive patients at the Central Magelang Public Health Center. The research method used a Quasi-Experimental design with a pre-post test with control group design approach. The measuring tools used were a sphygmomanometer and standard operating procedures (SOP). The sample was taken using purposive sampling technique, with a total of 76 respondents. The average reduction in systolic and diastolic blood pressure in the combination of Benson relaxation and aromatherapy group was 8 mmHg and 5.16 mmHg, respectively. Statistically, there were significant differences with a significance value of systolic blood pressure (p = 0.005) and diastolic blood pressure (p = 0.013), indicating that the combination of Benson relaxation and aromatherapy is effective in reducing blood pressure.